Next-Generation Sequencing Techniques to Diagnose Culture-Negative Subacute Native Aortic Endocarditis - Delphine Vetterli; Morgana Zennaro; Virginie Tacchini; Joannes Alexander Lobrinus; Virginie Prendki; Vladimir Lazarevic; Jacques Schrenzel (Emerging Infectious Diseases)
Next-generation sequencing might improve diagnosis of infective endocarditis. A case in Switzerland was initially attributed to Solobacterium moorei bacteria. Metagenomic analysis of the affected heart valve detected Streptococcus gordonii, but not S. moorei, illustrating that the results of molecular detection can vary depending on sampling time and anatomic site.